Oorzaken en enkele gevolgen van ontkerkelijking: Theoretische reflecties en empirische uitkomsten - de Graaf, Nan Dirk (Religie & Samenleving, 2013)
The secularization theory and supply side theory are considered to be each other’s opponents. I provide some critical reflections on the secularization theory and especially on the supply-side theory. In my opinion both theories offer useful insights to explain variations in religious disaffiliation. Unlike the popular approach of seeing both theories as each other’s opponents, I plea for an integration of both theories. In the second part of this contribution I discuss the consequences of religious disaffiliation for volunteering on the one hand and political behaviour of voters and political parties on the other. Research shows that religious people volunteer more than non-religious people. However, I will argue that it is too simplistic to assume a decline in volunteering similar to the decline in church membership. Furthermore, I show empirically that religious political parties are facing an increasing problematic dilemma: should they choose to stay close to their natural voters or should they try to maximize the numbers of votes?